Pengadopsian Standar Akuntansi Berbasis IFRS, Kepemilikan Keluarga, dan Manajemen Laba - Dwiyanti, Kadek Trisna (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 12 No 2 (2017), 2017)
Abstract This study examines the effect of IFRS adoption and family ownership on earnings management. This study also extends the current literature by examining the interacting effect between IFRS adoption and family ownership on earnings management. Data are obtained from Bloomberg database and Malaysia stock exchange for the period 2010-2013. Using multiple regression analysisis, this study found that firms exhibit less earnings management after IFRS adoption. This finding is consistent with the argument that IFRS are claimed to be high-quality accounting standards. However,t his study find no evidence to support that family ownership and interaction between IFRS and family ownership negatively affect earnings management . Keywords : IFRS adoption, family ownership, earnings management.